THE IMPACT OF SCHOOL WATCHING METHOD ON EARTHQUAKE DISASTER PREPAREDNESS ON PRIMARY SCHOOL STUDENTS AT SDN MOJOREJO 2 SRAGEN - Erika Dewi Noorratri; Irma Mustika Sari (Journal of Vocational Nursing, 2023)
Introduction: The world's largest archipelago, Indonesia is located on the equator between the plains of Asia and Australia and between the Pacific and Indian oceans. This geographical position can increase the danger of natural disasters such as tectonic earthquakes, volcanic eruptions, tsunamis, and so on. There are many consequences of eartquakes, on of which is that many buildings and destroyed or collapsed. School children can get involved in disaster preparedness at their schools because it is an effective, dynamic, and sustainable strategy that teaches kids to recognize the signs of disasters that happen around them from an early age. Disasters can occur anywhere, at any time, even in the middle of the school day. The aims of this study was determining the effect of the School Watching Method on earthquake disaster preparedness on Primary School Students, particularly at SDN Mojorejo 2 Sragen. Methods : The method employed was Quasy Experimental. The research design was a group pretest-posttest without control group design . there were 49 respondents and the sampiling used was total sampling. The research instrument used was a modified questionnaire from a questionnaire and a check sheet or preparedness observation from LIPI (S3) and UNESCO/ISDR. Results: The results of the dependents t test showed a p value of 0.0000, this meaning that there was a significant difference in average disaster preparedness after being given disaster education using the school watching method. Conclusions: The findings showed that there is an effect of the school watching method on earthquake disaster preparedness at SDN Mojorejo 2 Sragen.